Technical efficiency in maize production and its determinants: a survey of farms across agro ecological zones in northern Nigeria - Ibrahim, Kasim; Shamsudin, Mad Nasir; Yacob, Mohd Rusli; Radam, Alias (Asian Network for Scientific Information, 2014)
Most researches on agriculture focused on how to achieve certain level of yield. However, few researches consider rational resource allocation to improve efficiency. Considering the need to increase agricultural productivity through proper utilization of resources, this study measured the technical efficiency of maize production in northern Nigeria and identified the socioeconomic factors that determined technical efficiency in different agro ecological zones. The study was based on the conceptual framework that there is a relationship between input use and inefficiency in maize production in the area. Respondents were surveyed and data on input use, cost of production and yield were obtained. Stochastic frontier production function and Tobit models were used to analyze the data. The findings supported the conceptual framework that there is technical inefficiency in the use of inputs and certain socioeconomic factors contributed to inefficiency. The main contribution of the study is in measuring the technical efficiency of maize production from various States and modeling agro ecological zones to observe the impact of variation in climate and production practices on the technical inefficiency. The implication for the study is that farmers and policy-makers need to be rational on the use of inputs to achieve high level of technical efficiency.